(untitled) (Scientific journal of the Fergana State University, 2024)
Kara Darya is considered one of the most important rivers of the Fergana Valley. Based on our researches in the middle reaches of the Kara Darya and the analysis of the literature devoted to the study of ichthyofauna of the region, it was determined that 24 species of fishes belonging to 12 families and 6 genera can be found in the middle reaches of the river.